2021
DOI: 10.1111/bjd.19897
|View full text |Cite
|
Sign up to set email alerts
|

Dupilumab treatment in patients with atopic dermatitis: a comparative cohort study between the Netherlands and Japan shows a discrepancy in patient‐reported outcome measures

Abstract: Background Dupilumab was equally effective among all racial subgroups in clinical trials, but a direct comparison in daily practice is lacking. Objectives To investigate the effectiveness of dupilumab in patients with atopic dermatitis (AD) in the Netherlands and Japan over 80 weeks of treatment. Methods A longitudinal comparative cohort study was conducted in patients with AD who were treated with dupilumab in daily practice. We used linear mixedeffects models to determine changes over time. Results We found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…In turn, this finding suggests that annoying symptoms of the disease should not be neglected or overlooked even in the face of low EASI and SCORAD scores, confirming the need to consider patient‐reported outcome measures (PROMs) to understand fully the patient's overall experience of the disease. The recent findings about discrepancy in PROMs betterments among culturally different AD populations treated with Dupilumab, in face of comparable improvements in EASI scores, 35 are in line with what is stated here.…”
Section: Discussionsupporting
confidence: 91%
“…In turn, this finding suggests that annoying symptoms of the disease should not be neglected or overlooked even in the face of low EASI and SCORAD scores, confirming the need to consider patient‐reported outcome measures (PROMs) to understand fully the patient's overall experience of the disease. The recent findings about discrepancy in PROMs betterments among culturally different AD populations treated with Dupilumab, in face of comparable improvements in EASI scores, 35 are in line with what is stated here.…”
Section: Discussionsupporting
confidence: 91%
“…Physicians also underestimated the overall impact of AD on their patients’ QoL, with physicians estimating that 12–14% of their patients with moderate-to-severe AD had no QoL impact, compared with only 2–3% of patients indicating no QoL impact. In a previous study, patients reported that physicians sometimes underestimated the physical and emotional impact of AD on their well-being [ 35 ]. This is in line with a meta-analysis of nine studies in adults [ 36 ] and a more recent study that reported that physicians underestimated the QoL of children/adolescents with inflammatory bowel disease [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Japan, patients typically pay 30% of their medical expenses. A previous study reported that financial considerations were one of the primary reasons for discontinuation of DUP in Japanese patients ( n = 11/13) ( 2 ). However, the prognosis after discontinuation of DUP is unclear.…”
Section: Discussionmentioning
confidence: 99%